Apoptosis induced by the methanol extract of Salvia miltiorrhiza Bunge in non-small cell lung cancer through PTEN-mediated inhibition of PI3K/Akt pathway. (22nd March 2017) - Ye, Yin-Tao; Zhong, Wei; Sun, Pei; Wang, Dong; Wang, Chen; Hu, Li-Min; Qian, Jun-Qiang
Abstract: Ethnopharmacological relevance: Salvia miltiorrhiza Bunge, a well-known traditional Chinese medicinal (TCM) plant, has been used to treat cardiovascular diseases since thousands of years. Many studies reported that the active component tanshinones displayed a variety of biological activities: anti-thrombous, anti-allergic, anti-inflammatory, antioxidant and anti-tumor promoting. But the mechanism of how the active components working still need to be clarified. The anti-tumor effect of compounds of tanshinone (CTN), the methanol extract of Salvia miltiorrhiza Bunge roots, was investigated. The aim of this study was to investigate the effects of CTN on the growth inhibition, apoptosis and molecular targets of human non-small cell lung cancer (NSCLC). Materials and methods: CTN-induced cytotoxicity was determined by MTT assay. The cell survival was evaluated using clonogenic survival assay. The morphology of Glc-82 cells after treatment with CTN was determined by fluorescence microscopy. Cell cycle distribution was revealed by flow cytometry. The apoptotic cells were quantified with annexin V-FITC/PI staining and flow cytometry, and observed using Hoechst 33258 staining and TUNEL assays. The expression levels of proteins were analyzed using western blot. Tumor growth was assessed by subcutaneous inoculation of cells into BALB/c nude mice. Results: CTN inhibited the proliferation of NSCLC in a dose-dependent manner and induced both early and late apoptosis. Treatment of Glc-82 cells with CTN (5–80 μg/ml) significantly (p<0.05) suppressed the cell proliferation in a concentration and time-dependent manner. CTN induced significant (p<0.05) and dose-dependent apoptosis of Glc-82 cells. Cell cycle assay showed that CTN induced a G2 /M phase arrest, and significantly (p<0.05) increased expression of p53 and p21, actived caspase-3/9 and PARP1, which suggest the involvement of the mitochondria in the apoptotic signals. In addition, CTN decreased expression of the anti-apoptotic protein Bcl-2, Bcl-xl and increased expression of the pro-apoptotic protein Bax. Result also showed that CTN could increase expression levels of PTEN, and reduce the phosphorylated levels of Akt (protein kinase B) on Thr 308 and Ser 473 domain. In vivo assay showed that the antitumor effect of CTN was significantly augmented without increasing toxicity in nude mice bearing Glc-82 xenograft. Conclusion: The PTEN/Akt signaling axis is defined as a critical pathway regulated by PTEN in NSCLC. CTN, the methanol extract of Salvia miltiorrhiza Bunge, are the active compounds as shown by their ability to induce apoptosis through the mitochondrial pathway of apoptosis and PTEN-mediated inhibition of PI3K/Akt pathway. CTN could inhibit tumor growth more efficiently, which supports the ethno-medicinal use of this herb as an alternative or complementary therapy for NSCLC. Graphical abstract: